Analysis of vaccination coverage in Brazil in the period from 2018 to 2024 (Research, Society and Development, 2025)
The present study aimed to describe epidemiological data on vaccination coverage from 2018 to 2024, in order to identify possible variations in coverage rates, investigate significant changes during the pre-pandemic (2018–2019), pandemic (2020–2021), and post-pandemic (2022–2024) periods, and discuss potential factors that may have influenced these rates. The findings indicate that the decline in vaccination coverage was already apparent before the pandemic but was significantly intensified during the health crisis. Limited access to health services, fear of virus exposure, and the spread of misinformation contributed to decreased vaccination rates. After 2021, with the progress of COVID-19 vaccination and initiatives such as the High Vaccination Coverage Recovery Project (PRCV), a progressive recovery in coverage rates was observed. Despite improvements, many vaccines still fall short of recommended targets, particularly booster doses and second shots. The study also identifies persistent challenges, including vaccine hesitancy, structural issues in less developed regions, and limited public awareness of the importance of immunization. It concludes that Brazil possesses the technical capacity to restore high vaccination coverage levels, provided that well-structured public policies and educational campaigns continue.